Application Of Commercial Grade Ammonia Liquor In The Selective Non-Catalytic Reduction Of Nox In Combusted Gas From A Diesel Burner - Hossain, Khandoker Abul; Mohd. Jaafar, Mohammad Nazrim; Mustafa, Azeman; Ani, Farid Nasir (Penerbit UTM Press, 2005)

(untitled)
A pilot-scale investigation with Selective Non-catalytic Reduction (SNCR) of NOx were carried out by employing the aqueous solution of commercial grade ammonia liquor as NOx reducing agent in diesel burning exhaust at 6% excess oxygen and injection temperatures between 923 and 1323 K. The furnace simulated the small-scale combustion systems such as low capacity boilers, water heaters, oil heaters etc., which produce low level of baseline NOx usually below 100 ppm and where the operating temperatures remain within the investigated temperature range. With 5% aqueous ammonia solution, at a Normalised Stoichiomehic Ratio (NSR) of 4, as much as 57% reduction was achieved at an optimum temperature of 1063 K, which is quite significant for the investigated level of baseline NOx. The NOx reduction was observed to increase as the value of NSR increased. The residence time of the reagent has significant effect on the reaction performance, however, most of the reduction occurred within a short range of residence time and after that further increase in residence time showed very insignificant effect. The ammonia slip measurement showed that at optimum temperature and NSR of 4, the slip was about 18 ppm. The investigations demonstrate that commercial grade liquor ammonia is a potential NOx reducing agent, which could be used effectively and safely considering the health hazards.